2020
DOI: 10.1515/ldr-2019-0072
|View full text |Cite
|
Sign up to set email alerts
|

Islamic Social Finance in Bangladesh: Challenges and Opportunities of the Institutional and Regulatory Landscape

Abstract: From the end of World War Two, the core methodology of law and development projects has been to transplant the best legal institutions of Western capitalism to poor and emerging economies. In many post-colonial contemporary Muslim-majority countries, such programs have not adequately engaged with local legal systems, cultures and traditions. Contrary to the restrictive modernist approach to law and development, and inspired by the Sharia, there are numerous Islamic social finance mechanisms that can be utilise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Earlier, a field investigation on Amanah Ikhtiar Malaysia, one of the world's largest Islamic MFIs, based in Malaysia, provided new insights into the issues and challenges confronting women micro-entrepreneurs as clients of the Islamic microfinance industry [ 99 ]. An in-depth mixed-method analysis was also conducted in Bangladesh centred on regulatory and institutional aspects to identify the main factors impeding the achievement of Islamic social finance objectives and integration with the commercial sector, including the need for harmonisation and a clear regulatory framework [ 111 ]. Regarding risk management issues, stakeholders in Malaysia will accept the reality of unavoidable risk after all efforts have been exhausted provided the standard operating procedures were followed during the integration process [ 63 ].…”
Section: Finding and Discussionmentioning
confidence: 99%
“…Earlier, a field investigation on Amanah Ikhtiar Malaysia, one of the world's largest Islamic MFIs, based in Malaysia, provided new insights into the issues and challenges confronting women micro-entrepreneurs as clients of the Islamic microfinance industry [ 99 ]. An in-depth mixed-method analysis was also conducted in Bangladesh centred on regulatory and institutional aspects to identify the main factors impeding the achievement of Islamic social finance objectives and integration with the commercial sector, including the need for harmonisation and a clear regulatory framework [ 111 ]. Regarding risk management issues, stakeholders in Malaysia will accept the reality of unavoidable risk after all efforts have been exhausted provided the standard operating procedures were followed during the integration process [ 63 ].…”
Section: Finding and Discussionmentioning
confidence: 99%
“…This Islamic microfinance institution in village development praxis is found in Bangladesh, Malaysia, and Indonesia, which are majority Muslim population countries. The Islamic village microfinance institution contribution through rural development scheme, as has been done by Islamic Bank Bangladesh Limited (IBBL) in Bangladesh (Abdullah et al 2017;Hassan & Saleem, 2017;Anwarul Islam, 2016;Uddin & Mohiuddin, 2020), Rupali Bank Limited in Bangladesh (Nasrin & Sarker, 2014) and Amanah Ikhtiar Malaysia (Bhuiyan et al, 2011). It can be concluded that in the context of village development management, Islamic microfinance institution plays a major role in efforts to alleviate poverty in the Muslim world, most of whom live in villages.…”
Section: Discussion Of Research Themes Subthemes and Trends On Islami...mentioning
confidence: 99%
“…In this first theme, seven articles highlight the practice of institutionalizing Islamic principlesbased microfinance, which carries out its praxis in rural areas in Bangladesh as the first sub-theme ( (Abdullah et al, 2017), (Umar, Usman, & Purba, 2018), (Bhuiyan et al, 2011), (A. Hassan & Saleem, 2017), (Nasrin & Sarker, 2014), (Uddin & Mohiuddin, 2020)).…”
Section: Islamic Microfinance For Rural Development/poverty Alleviationmentioning
confidence: 99%
See 1 more Smart Citation
“…The author builds the concept of Islamic social bank on the theoretical perspective of Waqf as a tool for sustainable poverty eradication tool Abduh (2019). further establishes the role of Waqf based on Islamic social finance in financial inclusion Uddin and Mohiuddin (2020). tackle the regulatory constraints of implementing a Waqf based Islamic social finance model in an emerging country such a Bangladesh.…”
mentioning
confidence: 95%